On the use of a beam infiltration water intake structure for water supply purposes - Shamsutdinov Ruslan; Trotsenko Irina; Korchevskaya Yulia; Nazarkin Eduard (E3S Web of Conferences, 2021)
The object of research in this work is the under-channel waters of the Irtysh River, considered as an alternative source of water supply, necessary for the sustainable provision of high-quality drinking water to the population of cities in emergency situations. In bacteriological and sanitary-hygienic terms, studies have shown that infiltration waters are quite safe. According to the results of the analyzes carried out, infiltration waters are mainly fresh with a salinity of 0.5 to 1 g / l. The most rational scheme from a technical and economic point of view in relation to local conditions are beam water intake structures, which is due to the relatively low thickness of water-bearing rocks. At the same time, infiltration-type water intake structures in the Irtysh river valley should be located at a distance of up to 130 m from the river channel (taking into account the value of hydraulic resistance ∆lн). The distance between wells in a linear row should be taken up to 50 m.